The brides of London - Riley, Vanessa (Riley, Vanessa Advertisements for love series., 2021)
Bittersweet Bride: Widow Theodosia Cecil needs a husband to help protect her son. The former flower seller turned estate owner posts an ad in the newspaper, and no one is more surprised than she when her first love, the man she thought dead, reappears. Ewan Fitzwilliam has been at war for six years. Now, the second son of a powerful earl is back but his beloved Theo needs a husband and will not consider him. She believes Ewan left her--in desperate straits--so she denies the feelings she still harbors for the handsome, scarred soldier. Theo and playwright Ewan must overcome bitter lies and vengeful actions that ruined their youthful affair. Theo must reveal her deepest secret in order to reclaim the love that has long been denied.